2004
DOI: 10.12968/ijpn.2004.10.9.16049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of unrelieved patient suffering on palliative care nurses

Abstract: the nurses' stories indicate that the personal impact of unrelieved patient suffering could be reduced through acknowledgement of this suffering and better formal and informal support mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 14 publications
2
48
0
3
Order By: Relevance
“…2,3 Several explanations for this phenomenon have been put forth, including negative feelings on the part of providers, concerns regarding safety, efficacy and ease of utilization, inadequate knowledge on the part of healthcare professionals, and lack of administrative organization. [4][5][6][7][8][9][10][11][12][13] Under-adoption of interventions with a solid evidence base for benefit, including programs of PC, is an example of failure of translation of innovation into practice. Qualitative methods have proven Palliative care remains underutilized in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 Several explanations for this phenomenon have been put forth, including negative feelings on the part of providers, concerns regarding safety, efficacy and ease of utilization, inadequate knowledge on the part of healthcare professionals, and lack of administrative organization. [4][5][6][7][8][9][10][11][12][13] Under-adoption of interventions with a solid evidence base for benefit, including programs of PC, is an example of failure of translation of innovation into practice. Qualitative methods have proven Palliative care remains underutilized in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 PC work has numerous emotional demands that may lead to staff stress, including absorption of negative emotional responses, breaking bad news, challenges to personal beliefs, coping with inability to cure, immersion in emotional clashes, poorly defined roles, recurrent exposure to death, working in an area of uncertainty, patient suffering, and secondary trauma. [6][7][8] Ultimately, these demands affect staff emotional management, 9 and it is estimated that 50% of PC staff are at risk of poor psychological outcomes as a result of insufficient ability to cope with these demands. 10 This review aims to examine quantitative studies to explore the effectiveness of psychosocial interventions designed to improve psychological outcomes for PC staff.…”
Section: Introductionmentioning
confidence: 99%
“…7,[16][17][18]20,21 In this study, the participants identified their main goals as optimizing their patients' QOL and orchestrating a peaceful death for the patient. Bounded by the context of the nursepatient relationship, the participants observed, assessed issues, identified suffering, and intervened to relieve their patients' suffering.…”
Section: Discussionmentioning
confidence: 99%
“…2,[16][17][18][19][20][21] Interestingly, these studies revealed that participants did identify suffering at times, but when they did, they did not know what to do to alleviate it. Findings also revealed that the participants were affected by their patients' suffering and had difficulty coping with it.…”
Section: Introductionmentioning
confidence: 99%